SEJARAH PERPAT SERTA INDENTIFIKASI SOSIAL BUDAYA MASYARAKAT MELAYU BATAM 2000-2012 - Desma Yulia; Vivi Nalia (Universitas Riau Kepulauan, 2018)
Batam society shows pluralistic and different with Malay world existence. Perpat Perpat represent the real Malay world which has been lost. This reseach aims to know and understanding Perpat history parallel with social dynamic happened in early founding and understanding social cultural identification built by Perpat with historical perspective.This research uses history method. It done by 4 stages that are:1) Heuristic, that is sources collecting; 2) criticthat is sources validation; 3) interpretation that issourcesunderstanding; and 4) historiography that means historical writing process.This research results show that history of Perpat founding related with resistance of injustice to tempatan or local settlement. Moreover Perpat succeed show Malay identification process related with Malay social society in Batam area.Kata kunci: Perpat, Malay, identification